1998
DOI: 10.1002/(sici)1097-4679(199804)54:3<361::aid-jclp6>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

From the laboratory to the hospital, adults to adolescents, and disorders to personality: The case of psychological reactance

Abstract: Study 1 assessed whether trait reactance in disturbed adolescents (ages 12 to 17) is part of the same constellation of personality variables associated with reactance in adults, and Study 2 examined whether reactance predicts inpatient treatment duration and outcomes. Correlations between reactance and MMPI-A variables among 76 inpatients (41 girls) showed that reactance is associated with oppositional, nonaffiliative, and narcissistic traits in disturbed adolescents as well as adults. Reactance predicted long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…One potential approach for managing nonconscious reactance might be for high reactant individuals to learn to identify the situations that trigger reactance and plan in advance how to respond to these situations to minimize the chances of a behavioral backlash (e.g., see Gollwitzer's (1999) work on implementation intentions). Given that reactance can be highly inappropriate and possibly even detrimental to individuals and their relationship partners in many situations (Frank et al, 1998;Seibel & Dowd, 1999), future research might explore strategies to overcome automatic reactance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential approach for managing nonconscious reactance might be for high reactant individuals to learn to identify the situations that trigger reactance and plan in advance how to respond to these situations to minimize the chances of a behavioral backlash (e.g., see Gollwitzer's (1999) work on implementation intentions). Given that reactance can be highly inappropriate and possibly even detrimental to individuals and their relationship partners in many situations (Frank et al, 1998;Seibel & Dowd, 1999), future research might explore strategies to overcome automatic reactance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, individual measures of reactance are negatively correlated with improvement in a therapy situation and positively correlated with early termination of therapy (Seibel & Dowd, 1999). Moreover, reactance in disturbed adolescents is associated with oppositional, nonaffiliative, and narcissistic traits, longer hospital stays, aggression, mood problems, and substance abuse (Frank et al, 1998).…”
Section: Automatic Activation Of Goals By Significant Othersmentioning
confidence: 99%
“…However, Coulter and Pinto (1995) demonstrated that intense guilt appeals impair consequent attitude change compared to more moderate appeals, although moderate appeals were more effective than a no-guilt control condition. The problem is made worse by the fact that the incidence of reactivity is higher in delinquent groups (Frank et al, 1998) who are likely to engage in unhealthy and risk-taking behaviours (Jessor & Jessor, 1977).…”
Section: Reactancementioning
confidence: 99%
“…The tendency to experience PR is a personality trait (43), which is correlated with a range of phenomena including antisocial and narcissistic personality traits (44, 45) and with political conservatism (46, 47). The latter finding is not surprising given that conservative ideology, as compared to liberal ideology, strongly favors limited government intervention (29), and so government policies that threaten to restrict freedoms are likely to elicit PR (46).…”
Section: Introductionmentioning
confidence: 99%